The impact of artificial intelligence on banking services - Rakhimova Khavokhon Usmanzhonovna; Nomozov Umid Iskandarovich (THE INNOVATION ECONOMY, 2026)
This article analyzes the role and importance of artificial intelligence (AI) technologies in the banking sec tor. The introduction of AI in modern banking services is considered an important component of the digital trans formation process. AI technologies are considered as a tool that creates broad opportunities for providing personal ized services to customers, reducing risks and optimizing the loan portfolio. Also, the impact of AI-based automation of processes and analysis of large volumes of data on raising banking services to a new level, identifying risks and ensuring the stability of banking activities was studied. In addition, it is shown that the introduction of AI in the bank ing sector will serve not only to the emergence of new innovations, but also to increase the efficiency and competi tiveness of financial services in the future.